Expression of CD40 by the cells of benign and malignant breast tumors and antitumor action of autologous lymphocytes against chemoresistant and chemosensitive tumors - Bereznaya, N.M.; Kirnasovskaya, E.A.; Vinnichuk, Yu.D.; Belova, O.B.; Lukyanova, N.Yu. (Experimental Oncology, 2008)
Aim: To study the expression of CD40 by cells of benign and malignant tumors of mammary gland, and to compare the efficacy of lymphocytes antitumor activity against drug resistant and sensitive breast tumors in relevance to CD40 expression. Methods: Breast tumor explants were cultured with autologous lymphocytes in double diffusion chambers. The results were evaluated by morphological criteria of explants growth. Expression level of molecules on tumor cells was analyzed using immunohistochemical method (paraffin embedded slides), and on lymphocytes — by the method of indirect immunofluorescence. Results: The highest level of CD40 expression was detected on cells of chemoresistant malignant breast tumors, and the lowest one — on cells of benign breast tumors. The decreased CD40 expression on lymphocytes from patients with drug resistant breast cancer was compared with that on lymphocytes of the patients with drug sensitive breast cancer. The study of antitumor activity of autologous lymphokine activated killer cells (LAK) has shown their pronounced antitumor activity against drug resistant malignant breast tumors. Conclusion: Marked antitumor activity of LAK from the patients with drug resistant breast cancer is associated with high expression level of CD40 on tumor cells and with its decreased expression on lymphocytes. Цель: изучение частоты экспрессии CD40 клетками злокачественных и доброкачественных опухолей молочной железы и сравнение
эффективности противоопухолевого действия лимфоцитов в зависимости от экспрессии CD40 в отношении резистентных
и чувствительных опухолей молочной железы. Методы: культивирование эксплантатов опухолей молочной железы с аутологичными
лимфоцитами в двойных диффузионных камерах. Оценку результатов проводили на основании морфологических
критериев роста эксплантатов. Для определения экспрессии молекул на опухолевых клетках использовался иммуногистохимический
метод (парафиновые срезы), а на лимфоцитах — метод непрямой иммунофлуоресценции. Результаты: наиболее
высокий уровень экспрессии молекул CD40 отмечен на клетках резистентных злокачественных опухолей молочной железыпо
сравнению с опухолями, чувствительными к химиопрепаратам, а наиболее низкий — на клетках доброкачественных опухолей.
Установлено снижение экспрессии CD40 лимфоцитами больных со злокачественными резистентными опухолями молочной
железы по сравнению с лимфоцитами больных с чувствительными опухолями. На лимфоцитах больных с доброкачественными
опухолями уровень экспрессии CD40 был значительно выше по сравнению со злокачественными. Изучение противоопухолевой
активности аутологичных ЛАК показало, что противоопухолевое действие у больных со злокачественными опухолями, резистентными
к химиопрепаратам, было более выражено. Выводы: выраженная противоопухолевая активность ЛАК больных со
злокачественными опухолями, резистентными к химиопрепаратам, ассоциируется с высоким уровнем экспрессии CD40 на
опухолевых клетках и со снижением его экспрессии на лимфоцитах.